2013
DOI: 10.1063/1.4803089
|View full text |Cite
|
Sign up to set email alerts
|

Multi-channel transport experiments at Alcator C-Mod and comparison with gyrokinetic simulations

Abstract: Multi-channel transport experiments have been conducted in auxiliary heated (Ion Cyclotron Range of Frequencies) L-mode plasmas at Alcator C-Mod [Marmar and Alcator C-Mod Group, Fusion Sci. Technol. 51(3), 3261 (2007)]. These plasmas provide good diagnostic coverage for measurements of kinetic profiles, impurity transport, and turbulence (electron temperature and density fluctuations). In the experiments, a steady sawtoothing L-mode plasma with 1.2 MW of on-axis RF heating is established and density is scanned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 48 publications
2
55
0
Order By: Relevance
“…When the uncertainty in the experimental and simulated heat fluxes are considered, the multi-scale electron and ion heat fluxes are now found to be in quantitative agreement with the experiment. This result suggest that electronscale turbulence may explain the robust Q e under-prediction observed in this discharge [18][19][20][21] and demonstrates for the first time that, in realistic plasma conditions with significant ion-scale turbulence, electron-scale turbulence can drive experimentally relevant levels of electron heat flux.…”
Section: Simulation Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…When the uncertainty in the experimental and simulated heat fluxes are considered, the multi-scale electron and ion heat fluxes are now found to be in quantitative agreement with the experiment. This result suggest that electronscale turbulence may explain the robust Q e under-prediction observed in this discharge [18][19][20][21] and demonstrates for the first time that, in realistic plasma conditions with significant ion-scale turbulence, electron-scale turbulence can drive experimentally relevant levels of electron heat flux.…”
Section: Simulation Resultsmentioning
confidence: 94%
“…We emphasize that this plasma possesses no unique and experiment was identified in the ion heat and impurity particle channels while an underprediction (∼ 3×) was reported in the electron heat flux [19][20][21] . In these previous works, scans of the turbulence drive terms a/L T i , a/L Te , a/L n , n i /n e , and E × B shear were performed using ion-scale simulations (k θ ρ s < 1.3) to demonstrate that the under prediction of the electron heat flux is robust within experimental uncertainties.…”
Section: Experimental and Simulation Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…231,285 In this experiment, designed for validating gyrokinetic models of the energy and particle transport, a base-case steady, sawtoothing L-mode plasma with 1.2 MW of on-axis RF heating was established. When the density was raised by 20%, it was found that the measured rotation profiles changed from peaked to hollow in shape while the electron density and impurity profiles remain peaked.…”
Section: Momentum Transportmentioning
confidence: 99%
“…q i < 1. 5 While modifications of fluctuation spectra due to a change of turbulence regime have been reported from different diagnostics in various machines, [6][7][8][9] it was recently established that the ITG-and TEM-dominated regimes could be differentiated from the reflectometry spectra. 10 In the latter work, the experimental observations were supported by the non-linear gyrokinetic simulations, which qualitatively reproduced the shape of the reflectometry spectra in the ITG and TEM regimes.…”
Section: Introductionmentioning
confidence: 99%